2014
DOI: 10.1007/s00894-014-2375-5
|View full text |Cite
|
Sign up to set email alerts
|

Europium doped zinc sulfide: a correlation between experimental and theoretical calculations

Abstract: This paper presents the correlation among electronic and optical property effects induced by the addition of different concentrations of europium (Eu3+) in zinc sulfide (ZnS) by microwave-assisted solvothermal (MAS) method. A shift of the photoluminescence (PL) emission was observed with the increase of Eu3+. The periodic DFT calculations with the B3LYP hybrid functional were performed using the CRYSTAL computer code. The UV-vis spectra and theoretical results indicate a decrease in behavior of the energy gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…As can be seen in this figure, the spectrum for ZnS sample is highly asymmetrical, broadened and centred at ~ 504 nm, with multiple peaks indicating the involvement of different luminescence centers in the radiative processes. This spectrum exhibits similar features compared to that one reported by Ferrer et al [10], although reports from different groups have shown PL spectra of ZnS centred at lower wavelengths [1,2,[21][22][23][24]. According to Kripal et al, ZnS presents four blue-green emissions centred at 417, 446, 480 and 520 nm which arise due to interstitial S lattice defects, interstitial Zn lattice defects, S vacancies and Zn vacancies, respectively [1].…”
Section: Contributed Articlesupporting
confidence: 75%
See 2 more Smart Citations
“…As can be seen in this figure, the spectrum for ZnS sample is highly asymmetrical, broadened and centred at ~ 504 nm, with multiple peaks indicating the involvement of different luminescence centers in the radiative processes. This spectrum exhibits similar features compared to that one reported by Ferrer et al [10], although reports from different groups have shown PL spectra of ZnS centred at lower wavelengths [1,2,[21][22][23][24]. According to Kripal et al, ZnS presents four blue-green emissions centred at 417, 446, 480 and 520 nm which arise due to interstitial S lattice defects, interstitial Zn lattice defects, S vacancies and Zn vacancies, respectively [1].…”
Section: Contributed Articlesupporting
confidence: 75%
“…1. The calculated values are equal to 1.9, 1.8, 1.9, 1.9 and 1.5 nm for ZnS, ZM1, ZM3, ZM5 and ZM10, respectively, comparable to ZnS material prepared by the same method in a previous work [10]. The structure of Zn 1-x Mn x S samples was also characterized by XAS measurements.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, the photoluminescence (PL) properties are an important quantum optical phenomenon and are one of the most powerful methods for studying the order-disorder effects in semiconductors [8,9]. The doping process in semiconductors often causes significant alterations in the structural and electronic properties of these materials, and is the most promising strategy to further enhance their properties and applications in materials science [5,6,[15][16][17]. However, few studies have been reported on near-infrared (NIR) emissions for such particles [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth remembering that pure density functionals like GGA and LDA usually underestimate band gaps, while hybrid functionals, as the B3LYP used in this work, usually provide a good agreement with experimental values. 34,[48][49][50] However, calculations performed in parallel for β-PbO 2 using both B3LYP and HSE06 functionals gave a band gap value of 0.21 eV, while the experimental value is 0.61 eV. 4 Thus, both the functionals tried for us underestimated the β-PbO 2 band gap for about 66% respecting to the experimental value.…”
Section: -47mentioning
confidence: 81%